2021
DOI: 10.1016/j.omtm.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

UTX/KDM6A deletion promotes the recovery of spinal cord injury by epigenetically triggering intrinsic neural regeneration

Abstract: Interrupted axons that fail to regenerate mainly cause poor recovery after spinal cord injury (SCI). How neurons epigenetically respond to injury determines the intrinsic growth ability of axons. However, the mechanism underlying epigenetic regulation of axonal regeneration post-SCI remains largely unknown. In this study, we elucidated the role of the epigenetic regulatory network involving ubiquitously transcribed tetratricopeptide repeat on chromosome X (UTX)/microRNA-24 (miR-24)/NeuroD1 in axonal regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Primary cortical neurons were isolated from fetal mice (E14-16) as previously described ( Guo Z. et al, 2021 ). Briefly, the cortical brains of the fetal mice were removed and placed into a cold PBS solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cortical neurons were isolated from fetal mice (E14-16) as previously described ( Guo Z. et al, 2021 ). Briefly, the cortical brains of the fetal mice were removed and placed into a cold PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…Microglia could interact with almost all CNS cells during normal status and diseased development by transferring a large number of factors that are crucial for CNS function. One emerging novel propagating model of such cell-to-cell communication is through the release of exosomes ( Guo Z. et al, 2021 ). Microglia-released exosomes can be taken up by neurons and affect recipient cell neurogenesis and neuronal cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Tests were performed three times with an interval of 10 min before model induction and on days 1, 3, and 7 and once per week thereafter for 8 weeks post SCI. The hindlimb motor evoked potential (MEP) and latent period were obtained as previously described ( Guo et al, 2021 ). Briefly, recording needle electrodes were inserted intramuscularly into the tibialis anterior muscle of the hindlimbs.…”
Section: Methodsmentioning
confidence: 99%
“…10 It has been reported that knockdown of the epigenetic factor Ubiquitously Transcribed tetratricopeptide repeat on chromosome X (UTX) can facilitate axon regeneration and angiogenesis after acute spinal cord injury by targeting microRNA-24. 11,12 Epigenetic modifications are also involved in angiogenesis after chronic compressive spinal cord injury through the Xist/miR-32-5p/Notch-1 axis. 13 Among epigenetic modifications, N6-methyladenosine (m6A) is the most common and abundant mRNA modification.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting HDAC1 was found to promote neuronal loss and DNA damage, which further deteriorated behavioral outcomes after stroke 10 . It has been reported that knockdown of the epigenetic factor Ubiquitously Transcribed tetratricopeptide repeat on chromosome X (UTX) can facilitate axon regeneration and angiogenesis after acute spinal cord injury by targeting microRNA‐24 11,12 . Epigenetic modifications are also involved in angiogenesis after chronic compressive spinal cord injury through the Xist/miR‐32‐5p/Notch‐1 axis 13 …”
Section: Introductionmentioning
confidence: 99%